Pembelajaran Bahasa Arab di Provinsi Lampung Tahun 2016 - Akla, Akla (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2017)
This research aims to reveal the data of Arabic language learning in Lampung. This research is focused on teachers professionality, Arabic learning process, and students’ Arabic language skills that consist of istima’, kalam, qira’ah, and kitabah. This research refers to a survey study by collecting information from sample through questionnaire. The objectives of this research not only examine the map of teachers professionality, Arabic learning process, and students’ Arabic language skills but also find out the interaction between learning process and students’ Arabic skills. The samples of this research were 49 Arabic teachers and 382 students of Islamic Senior High School around Lampung. From the results of analysis data, it can be concluded that teachers professionality belongs to medium level, Arabic learning process belongs to medium level, students’ Arabic language skills belong to low level. The results of associative analysis showed that there is a significant influence between learning process and students’ Arabic language skills; therefore, it can be regarded that un-maximal learning process and environment have an impact towards the students low-level Arabic language skills.